STUDY OF THE QUALITATIVE CHARACTERISTICS OF THE MAXILLA BONE TISSUE ACCORDING TO THE QUANTITATIVE CONTENT OF MACROELEMENTS (P, NA, CA, MG, S) IN THE DYNAMICSOF PRENATAL ONTOGENESIS - Oshurko, A.P.; Oliinyk, I.Yu. (World of Medicine and Biology, 2019)
The germs of the maxillas of 131 fetuses in the age of 11-40 weeks of fetal development have been investigated in order to determine the quantitative macroelements (P, Na, Ca, Mg, S) content in the dynamics of prenatal ontogenesis. The bone tissue sampling was carried out on the both sides of the upper jaw germ of human fetuses from different areas, that had macroscopically the most marked density. A complex of methods of morphological research was applied, which included macroscopy, morphometry, fine preparation of objects under the control of loupe were used during the investigation; methods of flame atomic emission and atomic absorption analysis; photometric and turbidimetric methods; the method of statistical groupings in the study of qualitatively homogeneous aggregates, the variational analysis of statistical data with the calculation of average values for each macroelement, the errors of the average values, the reliability of the average values and the probability of accurate prognosis. A significant difference was found in the dynamics of the fetal period of prenatal ontogenesis between the indices of macroelements content, which is a qualitative result of quantitative morphology in determining their content during the study of the upper jaw bone tissue in human fetuses. The regularity of the dynamics of the upper jaw bone density of human fetuses, depending on the mineral content and the presence of the revealed synchronism of these processes, suggests that the change in density is the evidence of a change in the content of individual mineral elements, but the macroelements (Ca, P, Na, Mg, S), as the main building material are the most important. The obtained results are well-grounded and can be the basis for developing new methods of early diagnosis of congenital anomalies of the maxillofacial area in the preclinical stages of its development and methods of their prevention, by correcting the mineral content.